The Influence of Social Environmental Factors, Parenting Patterns, Education, Nutrition, and Culture on the Holistic Development of Early Childhood - Nafi'atussa'adah, Roihana; Eva Latipah; Ilahy, Ahda Dana (Linguanusa : Social Humanities, Education and Linguistic, 2025)
Introduction to The Problem: This phenomenon holds significant importance, given the complexity of the Indonesian socio-cultural context and the existing disparity in the quality of Early Childhood Education (ECE) services. Purpose: This study is designed to meticulously explore the intricate interactions among social environmental factors, parenting practices, education, nutrition, and culture in shaping the holistic development of early childhood. Design/methods/approach: The research employed a qualitative approach, utilizing a combination of narrative inquiry and case studies. Data collection involved semistructured interviews, participatory observation, and documentation targeting 12 participants, comprising parents, ECE teachers, and administrators of early childhood education institutions within Sleman Regency. Purposive and snowball sampling techniques were utilized to select the relevant informants. Data analysis was performed thematically, based on the interactive model proposed by Miles & Huberman. Findings: Five core themes were identified: (1) The quality of the social environment supporting socio-emotional development; (2) Democratic parenting practices fostering independence and self-expression in children; (3) Local culture-based ECE reinforcing children’s identity and engagement; (4) Nutritional consumption patterns impacting children's focus and participation; and (5) Cultural values serving as instruments for character education. These findings affirm that child development is the result of an intricate system that is socio-economically and culturally interconnected. Research implications/limitations: It is recommended that future research thoroughly investigate the spiritual and religious dimensions of holistic child development. Originality/value: The primary contribution of this study is the enrichment of Bronfenbrenner’s ecological theory and social constructivism within the local Indonesian context, alongside providing an empirical foundation for designing highly contextualized community-based interventions..